The meaning of health care as a result of social interaction - Herrera Paredes, José Manuel (2023)
Speaking of health care, it is convenient to recognize the influence that the meanings that people have generated about health and disease have on it from the interaction with their context and previous experiences with similar situations of their own or others, for which this part of how the health situation is perceived based on its meanings, it is essential to keep it in mind when providing the care that nursing professionals provide to their patients, since the success or failure of the interventions is directly related to observing these meanings. That is why, through Herbert Blumer's symbolic interactionism, it is intended to help understand that the meaning of health care has its origin in social interaction and the importance that this has in order to understand the behavior of people in specific situations, like health care.